Spatial Analysis of Land Ownership on Spatial Patterns (Coastal Borders) from 2012-2032 in Aceh Besar Regency - Akbar Maulana; Sugianto Sugianto; Muhammad Rusdi (Pascasarjana, Mataram University, 2023)
This study aims to analyze land ownership in 2022, mainly in the area of Mesjid Raya District of Aceh Besar Regency. This study used a descriptive survey method. This study's results indicate that nine out of 4,208 Land Ownership Rights in the Mesjid Raya District (0.225%) have buildings on them. Therefore, the issuance of Land Ownership Certificates in Coastal Border Areas violates laws according to Government Regulation No. 16 of 2004 and Circular Letter No.4 SE-100.PG.01.01/II/2022 regarding Land Use Policy in Protected Areas. The nine types of Land Ownership Rights issued in the Coastal Border Areas are divided into four certificates of Ownership Rights and five certificates of Usage Rights, and they are located in several villages, such as two certificates in Neuheun, two certificates in Ladong, two certificates in Ruyung, one certificate in Meunasah Keudee and one certificate in Lamreh. The total area of the Ownership Rights Certificates issued in the Coastal Border Areas is 21,206 m2, and the total area of the Usage Rights Certificates is 145,302 m2.